Spray‐coated PDMS/PVDF composite membrane for enhanced butanol recovery by pervaporation. Issue 4 (18th August 2020) - Cheng, Chi; Yang, Decai; Bao, Meiting; Xue, Chuang
Abstract: In this study, spray‐coating was used to prepare dihydroxypolydimethylsiloxane (PDMS) composite membranes with high flux and separation factor for biobutanol recovery from aqueous solution. A thin, smooth, and defect‐free PDMS layer was prepared by spray‐coating on polyvinylidene difluoride ultrafiltration membrane with little PDMS penetration. The effects of process parameters for membrane fabrication and pervaporation on membrane performance were investigated. A membrane with 2 μm active layer was obtained with a high flux of 1306.9 g/m 2 h. The optimal membrane with the highest pervaporation separation index (PSI) (19.15 kg/m 2 h) showed a total flux of 530.6 g/m 2 h and a separation factor of 36.1 at 37°C, and a PSI of 65.61 kg/m 2 h and a flux of 1927.0 g/m 2 h at 70°C. Membrane performance was affected by feed composition and temperature. Acetone‐butanol‐ethanol solution and fermentation broth gave lower butanol fluxes and separation factors compared to butanol model solution. Abstract :